The consequences of free trade in manufactures between Israel and the EEC - Richard Pomfret (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1976)
In 1975 Israel and the EEC signed a preferential trade agreement, which included provision for free trade in manufactured goods between the signatories by 1989 at the latest. The present study examines the economic consequences for Israel of such a free trade area. Although political factors are clearly important in determining the course of EEC-Israel relations, analysis of their economic aspects is facilitated by abstracting from the political issues. Within this framework, the free trade area can be seen as a case of mutual preferences between a large economically developed bloc and a small semi-industrialized country. During the 1960s economists and policy-makers, dissatisfied with the results of industrialization by import substitution, began to advocate the export of manufactures according to comparative advantage as a suitable development strategy for the less-developed countries (LDCs). A major obstacle to the success of this strategy was considered to be the tariff barriers existing in the high-income countries, where the largest markets lay, and the UN Conference on Trade and Development expended much energy between 1964 and 1971 in negotiating a system of preferential tariffs to be offered to LDCs. The intention was that eighteen developed countries would participate in the common system, but lack of agreement led to each country or bloc adopting a separate scheme. The individual preference systems which have emerged have come under a great deal of criticism, because they exclude some manufactured goods (usually the ones in which the LDCs have a comparative advantage) and place ceilings on preferential trade in other goods.
Keywords: 330